Quantification of nutritional intake during a congested fixture period in players from the English Premier League - Anderson, L.; Orme, P.; Naughton, R.; Close, G. L.; Louis, J.; Morgans, R.; Drust, B.; Morton, J. P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Muscle glycogen is the primary energy source during soccer match play (Krustrup et al. 2006). In times of fixture congestion (i.e. consecutive matches every 2-3 days), it has therefore been suggested that soccer players consume high daily carbohydrate (CHO) intake (>6 g/kg) in an attempt to promote muscle glycogen re-synthesis and match day physical performance (Anderson et al. 2015). The aim of this study was to therefore quantify daily energy intake and macronutrient composition in English Premier League (EPL) soccer players undergoing a period of fixture congestion. Methods: Six professional EPL (from one team) soccer players (mean ± SD; age: 27 ± 3 years, body mass: 80.5 ± 8.7 kg, height: 180 ± 7 cm, body fat: 11.9 ± 1.2%, lean body mass, LBM: 65.0 ± 6.7 kg) completed daily food diaries alongside the remote food photographic method (RFPM) over a 7-day period consisting of 2 competitive games (Day 2 and 5) and 5 training sessions (Day 1, 3, 4, 6 and 7). Data were analysed for total daily energy, CHO, protein and fat intake using dietary analysis software (Nutritics Ltd, Ireland). Results: Energy intake was greater on (P<0.05) match days (MD) (3789 ± 577 kcal and 61.1 ± 12.5 kcal/kg LBM) compared with training days (TD) (2948 ± 686 kcal and 45.2 ± 12.2 kcal/kg LBM, respectively). Similarly, CHO intake was also greater (P<0.05) on MD (6.4 ± 2.2 g/kg) compared with TD (4.2 ± 1.6 g/kg). In contrast, neither protein (2.7 ± 0.4 g/kg v 2.5 ± 0.7 g/kg) nor fat intake (1.5 ± 0.6 g/kg v 1.2 ± 0.2 g/kg) was different between MD and TD, respectively. CHO intake during matches (35.8 ± 21.5 g/min) was also different (P<0.05) from that consumed during training sessions (5.5 ± 10.3 g/min). Discussion: In accordance with current sports nutrition guidelines (Burke et al. 2011), we conclude elite soccer players consume apparently adequate energy and CHO intake for the typical loads observed on MD versus TD. However, on the basis of a congested fixture period (i.e. 2 days between games), we suggest players should consume higher daily energy and CHO intakes (similar to those reported on MD) on TD between matches so as to promote glycogen re-synthesis in recovery from match play and prepare for the subsequent game.